Estimation of the vine-shoot yield in the Gyöngyös district - Gonda, Cecília (Acta Agraria Debreceniensis, 2013)
Every year, a significant amount of vineyard prunings is generated in Hungary. Instead of utilization them, it is burned directly on the field in spite of the limitations of legalization highly pollute the environment in recent decades. The vineyard pruning itself or with other by-products from pomology and forestry can be significant amount of fuel source. However, before the planning to utilization the essential task is to estimate the potential. This study examine that how many vineyard is generated in the micro-region of Gyöngyös in every year on appointed vineyard.In order to vine-branch potential calculate more accurate data was necessary so the products had to be determined for all plant. Thus, the biomass resource and the utilization become plannable. As the result of the experiment we can estimate that 1,5 t/ha vineyard pruning are generated. It means more than 9 thousand tons pruning in the micro-region of Gyöngyös. This amount can be convert into fuel source more than 150 thousand GJ heating value.The results evince that the vineyard pruning is important fuel source in every year in the micro-region of Gyöngyös. Further usage is suggested for other regions in other size.